2021
DOI: 10.9734/jpri/2021/v33i31a31671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agmatine on Non-Alcoholic Fatty Liver Disease Induced by Type 2 Diabetes in Rats

Abstract: Aim: To determine the potential hepatoprotective effect of Agmatine (AGM) on NAFLD-induced by Type 2 diabetes mellitus (T2DM) in rats. Study design:  Forty male Wistar rats weighing from (200 -250 g) were distributed at random into five groups (8 rats per group): group 1 as control; group 2 as untreated-T2DM; groups 3 & 4 as T2DM cotreated with AGM (40 & 80 mg/kg/d), while group 5 T2DM cotreated with Silymarin (100 mg/kg/d). Place and duration of study: Department of Pharmacology, Faculty o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In most of these studies, AGM (at dosages 20-100 mg/kg) was administered intraperitoneally or orally to adult rats. Moreover, previous preclinical studies showed that daily oral delivery of AGM is safe and increases brain and plasma AGM levels (Aglawe et al, 2021;Barua et al, 2019;Bergin et al, 2019;Miski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In most of these studies, AGM (at dosages 20-100 mg/kg) was administered intraperitoneally or orally to adult rats. Moreover, previous preclinical studies showed that daily oral delivery of AGM is safe and increases brain and plasma AGM levels (Aglawe et al, 2021;Barua et al, 2019;Bergin et al, 2019;Miski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%